The investigation of inorganic elements composition in Carduus nutans L. and Carduus acanthoides L. flores and leaves - T. I. Balanchuk; A. V. Мazulin; Т. V. Оproshanska; G. V. Мazulin (Zaporozhye State Medical University, 2017)
Aim. The flowers and plant leaves of Carduus nutans L. and Carduus acanthoides L. during flowering are perspective for identification, investigation and quantitative assay of biologically active inorganic elements by atomic emission spectroscopy (AES) methods. Methods and materials. Accumulation of inorganic macro- and microelements in flowers and leaves of genus Carduus L. of Ukraine flora: Carduus nutans L. and Carduus acanthoides L. has been studied. Drying was conducted on setting "Termolab SNOL 24/350" (Україна), (t = 40 °С) 15 hours. The atomic emission spectroscopy (AES) method by DFS-4 with IBC-28, has been used for research. Results. The content of 15 macro- and microelements has been determined in flowers and leaves of Carduus nutans L. and Carduus acanthoides L. Sufficiently high content of macro- and microelements (К, Са, Mg, Fe) has been noted. Flowers and leaves of Carduus nutans L., Carduus acanthoides L. contain the inorganic element (Sr) in chronic values; the inorganic elements (Pb, Co, Cd, As, Hg) in insignificant concentrations. Conclusions. The flowers and plant leaves of Carduus nutans L., Carduus acanthoides L. are perspective for inorganic elements (К, Са, Mg, Fe) determinations by atomic emission spectroscopy (AES) methods. The inorganic chemical elements are required for normal human life and the hepatoprotective and antioxidant effects of herbal extracts. The accumulation of inorganic elements (Sr, Ni, Pb, Co, Cd, As, Hg) does not exceed the permissible levels of toxic. The parts of Carduus L. genus: Carduus nutans L. and Carduus acanthoides L. are important medicinal plants for identification and quantitative assay оf toxically inorganic elements.